Laporan Kualitas Audit dan Opini Audit Terhadap Kualitas Laporan Keuangan PT. Nayra Multi Jaya Payakumbuh - Agustina Sitompul; Yudi Prayoga; Bhakti Helvi Rambe (CV. Ulil Albab Corp, 2024)
The aim of the research is to examine the influence of audit quality and audit opinion on the quality of PT's financial reporting. Nayra Multi Jaya Payakumbuh. The sample for this research consisted of 50 samples, namely all employees at PT. Nayra Multi Jaya Payakumbuh. The research method used is quantitative and processed using the SPSS 26 program. The independent variables are audit quality and audit opinion, and the dependent variable is the quality of financial reporting. The test results of this research show that audit quality and audit opinion have a significant influence on the quality of PT's financial reports. Nayra Multi Jaya Payakumbuh.